The Correlation Between Students’ Self-esteem and Their Speaking Skill at Grade XI of SMA PGRI Pekanbaru - Anggie Rayanti Sesilia Haro Munte; Pahmi Pahmi; Siti Niah (Jurnal Pendidikan Amartha, 2025)
This study aims to investigate the relationship between students’ self-esteem and their English-speaking skills among eleventh-grade students at SMAN PGRI Pekanbaru. It seeks to determine whether self-esteem significantly influences students’ ability to perform in spoken English.This research employed a quantitative correlational design to examine the correlation between two variables: students’ self-esteem (independent variable) and speaking skills (dependent variable). Data were collected through a self-esteem questionnaire and a speaking skills test administered to class XI students. The questionnaire was completed within a 15-minute time allocation. Statistical analysis, specifically Pearson Product-Moment Correlation, was used to analyze the relationship between the variables.The findings reveal a very strong positive correlation between students’ self-esteem and their speaking skills, with a correlation coefficient (r) of 0.999 and a significance value of 0.000 (p < 0.01). Since the significance value is lower than 0.05, the alternative hypothesis (Ha) is accepted. This indicates that higher levels of self-esteem are associated with better speaking performance among students. Therefore, students’ self-esteem has a significant positive influence on their English-speaking skills.This study highlights the importance of fostering students’ self-esteem to improve their speaking abilities in English learning contexts. Teachers are encouraged to implement strategies that build students’ confidence and self-worth to enhance their oral communication skills. However, this research has several limitations. First, time constraints affected data collection, as students had limited time (15 minutes) to complete the questionnaire, which may have influenced the accuracy of their responses. Second, difficulties in obtaining administrative data and cooperation from the school management posed challenges during the research process. Future studies are recommended to allow more flexible time allocation and ensure better institutional support to improve data quality and research effectiveness.